Pregnancy and delivery complications and treatment approach in attention deficit hyperactivity disorder - Aktepe, Evrim; Ozkorumak, Evrim; Tanriöver-Kandil, Sema (The Turkish Journal of Pediatrics, 2009)
Pregnancy, delivery complications and treatment approach were evaluated in 153 cases diagnosed with attention deficit hyperactivity disorder in the State Hospital of Antalya in the Child and Adolescent Psychiatry Polyclinic. Most of the cases had been delivered vaginally (74.5%). The most frequent delivery complication was asphyxia/hypoxia (15.6%). The agent most frequently preferred in the treatment regimen was methylphenidate (82.4%), which is a psychostimulant. The other drugs used were risperidone (29.4%), selective serotonin reuptake inhibitors (16.4%) and imipramine (4.6%). The most frequent side effect resulting from methylphenidate use was a decrease in appetite (34.9%). Attention deficit hyperactivity disorder often presents with comorbid disorders; in these cases, nonstimulant agents had to be added to methylphenidate for better treatment outcomes. Use of selective serotonin reuptake inhibitors in combined treatment and in cases with comorbidities is in agreement with the literature. Further studies of combined treatment regimens in attention deficit hyperactivity disorder are needed.